(3GdacQ GdEOGQj hGdEOGQI aj GdJWHjb GdYdej s - (3eMehO Cejf(B, (3Rhjds ((3GdGScfOQjI(B:s (3OGQ GdeYGQa GdMOjKI(B,s)
(3JbOje JWhQ GdacQ GdEOGQj,hXGFa GdEOGQI,GdJJNWjW,CfhGY GdNWW,GdJfXje,JTcjd GdgjFI GdEOGQjI,GdJhLjg,GdQbGHI,eYGdLI HYV GdehGba GdEOGQjI aj GdJWHjb,eYGdLI GdeTcdGJ GdEOGQjIs
(3HjHdjhZQGajG U(B.144s
Keywords: (3GdEOGQIs; (3GdJNWjWs; (3GdJfXjes; (3GdQbGHI GdEOGQjIs